CHILDREN'S MEANING MAKING PROCESS TO ENGLISH LEARNING:A SYSTEMATIC REVIEW - Seidel Bortolotti, Fernanda; de Toni, Plinio Marco (Revista de Letras Norte@mentos, 2023)
This paper aims to gather findings regarding the meaning making process children face while engaged in learning English. Three keywords were adopted: “meaning making process”, “bilingual children” and “English language learners (ELL)”. Ten references were included, nine from the United States (US). The learners were supposed to have previous experience with another language and Spanish was the most cited. The results point to translanguaging as a trend. Emergent bilinguals, minority and majority languages are cited as suitable terms, while ELL and others should become obsolete. To capture different learning environments, future study could exclude results from the US.